Recess environment and curriculum intervention on children's physical activity: IPLAY. Issue 2 (10th April 2018) - Nigg, Claudio R; Kutchman, Eve; Amato, Katie; Schaefer, Christine A; Zhang, Guangxiang; Anwar, Md Mahabub Ul; Anthamatten, Peter; Browning, Raymond C; Brink, Lois; Hill, James
Abstract : Schoolyard renovations and a physical activity recess curriculum alone and in combination did not have an effect on children's physical activity. Abstract: Understanding the impacts of the built environment on physical activity (PA) is essential to promoting children's PA. The purpose of this study was to investigate the effects of schoolyard renovations and a PA recess curriculum alone and in combination on children's PA. This was a 2 (learning landscape [LL] vs. non-LL) × 2 (curriculum intervention vs. no curriculum intervention) factorial design with random assignment to the curriculum intervention, and six elementary schools per condition. PA outcomes were assessed preprogram, mid-program, immediate postprogram, and one year postprogram. No meaningful intervention effects were found. Lack of an effect may be due to the brief dose of recess, the curriculum not being integrated within the schoolyard, the LL implementation occurring prior to the study, or the already high levels of PA. Potential avenues to promote PA include making recess longer, integrating recess into the school curricula, and developing recess PA curricula integrating schoolyards.